Current Surgical Treatment and Outcomes for Functional Tricuspid Regurgitation. Issue 2 (4th March 2018) - Weir, William B.; Romano, Matthew A.; Bolling, Steven F.
ABSTRACT: Functional tricuspid regurgitation (TR) is a consequence of asymmetric dilation of the tricuspid annulus due to right ventricular dysfunction and enlargement from valvular and myocardial abnormalities of the left heart. Even if TR is negligible at the time of left-sided valvular surgery, it can worsen postoperatively and appear late, which implies a poor prognosis. Surgery for functional TR is underutilized, despite data demonstrating poorer outcomes in the face of residual TR. When performed, common repair techniques include placement of a rigid or semi-rigid annular ring, which have superior longevity compared with suture and flexible band repair techniques.